Humanity: art and humanity / Dr. Muhammad Fauzan Abu Bakar - Abu Bakar, Muhammad Fauzan (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The collection of artworks by Gerald Goh Teck Joo, Liew Kim Phiaw, Chrisna Pindah, Stewart Fung Sai Weng, and Sylvester Wielding Anak Jussem forms a cohesive exploration of humanity through the lens of cultural identity, tradition, and the relationship between the past and present. The reflection begins with Gerald Goh’s insight in "The Ambassador," where humanity is seen as more than a set of cultural symbols or physical representations. Goh moves beyond the visible markers of culture like traditional attire or objects, instead pointing to the simple, sincere gestures of kindness, warmth, and pride that define how people relate to one another. Building on this idea, Liew Kim Phiaw’s "Penghormatan Roh Leluhur" takes us deeper into the spiritual dimension of humanity, focussing on rituals that preserve the connection between the living and their ancestors. This artwork underscores that maintaining these rituals is essential to sustaining the cultural fabric of a people, drawing attention to the human need for continuity and respect for those who came before.